2006
DOI: 10.1115/1.2212438
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Unglazed Transpired Collector on the Performance of a Polycrystalline Silicon Photovoltaic Module

Abstract: The electrical power generated by a polycrystalline silicon photovoltaic (PV) module mounted on an unglazed transpired solar collector (UTC) has been studied and compared to that of a PV module without UTC for a quantitative analysis of electrical output and its role in reducing the simple payback periods of photovoltaic electrical systems. A 75W polycrystalline silicon PV module was fixed on an UTC in front of the ventilation fan, and effectiveness of cooling by means of the forced ventilation at the rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…However, the project was terminated prematurely when it was decided that Solarwall as a Canadian company could not apply for PV:BONUS grants. In a cooperation with KIER, an evaluation of the perforated collector with c-Si PV is presented by Naveed et al [240].…”
Section: Air Collectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the project was terminated prematurely when it was decided that Solarwall as a Canadian company could not apply for PV:BONUS grants. In a cooperation with KIER, an evaluation of the perforated collector with c-Si PV is presented by Naveed et al [240].…”
Section: Air Collectorsmentioning
confidence: 99%
“…Naveed et al [240] examined a PVT air system in which PV was connected to an unglazed transpired collector. It was found that a temperature reduction of 3-9 1C resulted in an improved electrical performance, allowing a reduction in PV area from 25 to 23 m 2 .…”
Section: Chow (2005) Calculated the Electrical Performance Of A Thermmentioning
confidence: 99%
“…Augustus ve Kumar, hava sızdırmalı güneş toplayıcılarının ısıl performans analizini ve matematiksel modellemesini geliştirmişlerdir [21]. Naveed ve arkadaşları, fotovoltaik modüllü hava sızdırmalı güneş toplayıcısının performans analizini yapmıştır [22] [34]. Gao ve arkadaşları, soğuk iklim koşullarında kaplamalı hava sızdırmalı güneş toplayıcılarının hacim ısıtma performansını test etmiştir [35].…”
Section: Introductionunclassified
“…In one study, the forced ventilation of polycrystalline silicone PV modules using a TSC system was able to reduce the operating temperature of the PV modules by 3-98C. This cooling of the PV modules resulted in a reduction in simple economic payback time from 23 years (PV without TSC) to 15 years (PV/TSC) (Naveed et al, 2006).…”
Section: Photovoltaic Tscsmentioning
confidence: 99%
“…The aim of creating a hybrid PV/TSC system is to develop a device that can simultaneously convert solar radiation into economical heat and electricity when available collector area is at a premium (Charalambous et al, 2007), or simply to improve the economic performance of the PV system by cooling the PV cells (Naveed et al, 2006). There are two broad types of PV/TSC g bonded type -PV cells/modules are bonded directly to the absorber (Delisle, 2008;Hollick, 1998) g fixed type -PV modules are fixed to the absorber (CEI, 2010b;Naveed et al, 2006).…”
Section: Photovoltaic Tscsmentioning
confidence: 99%